Structural Framework for Measuring the Performance of Information Systems â€“ Case Study - Falih, N.; Abouhilal, A. (International Journal of Engineering and Technology, 2018)
Measuring the performance of Information System (IS) is considered as one of the main pillars of the IS governance in the company. Key performance indicators (KPI) are the most used tools for measuring IS performance. In this work, we propose a structural framework based on the extended ISO 194400 Meta-model that can provide a multiview meta-knowledge library, to enrich all the company dashboards for decision-making. In practice, we propose a case study in a Moroccan telecom company for deploying the proposed structural approach. We use especially Galois lattices in order to evaluate the synchronization level between some processes and key performance indicators as a contribution to measuring the performance of Information Systems.Â Â